(untitled) (Praxis Educativa, 2025)
Academic mobility is strongly related to migratory phenomena (internal and international) and to social inequality. In this article we analyze different social uses of outgoing academic stays of students at the National University of Córdoba. The empirical material is based on a survey and interviews with young people who have made their stays abroad through internationalization programs. First, we will contextualize the factors that shape student mobility scenarios. Then, we will analyze the successive mobilities of students who stayed in different destinations. Finally, we will problematize the complexity of motivations behind these practices.